Improving Digital Literacy for Village MSMEs through Social Media-based Marketing Training - Moh Fatkhur Rokhzi (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This community service activity aims to improve the digital literacy of Micro, Small, and Medium Enterprises (MSMEs) in rural areas through social media-based marketing training. Lack of digital skills is a major obstacle to MSME development in the digital economy era, particularly in promotion and market expansion. The implementation method for this activity included needs identification, technical training on the use of social media (Instagram, Facebook, and WhatsApp Business), and mentoring in implementing simple digital marketing strategies. The results of the activity demonstrated a significant increase in participants' understanding of how to use social media as a means of product promotion. Participants were also able to create creative marketing content, improve customer interactions, and understand the importance of digital identity and ethical communication in cyberspace. Thus, this training contributes to increasing the competitiveness of rural MSMEs and supports the acceleration of digital transformation in the local economic sector.